Uji Daya Hasil Sepuluh Galur Baru Tanaman Padi (Oryza Sativa L.) Rakitan Politeknik Negeri Lampung - Eka Erlinda Syuriani; Risa Wentasari; Jaenudin Kartahadimaja (Politeknik Negeri Lampung., 2013)
Rice is the staple food of Indonesia's population. Widespread food shortages in a country will lead to economic insecurity, social and political. Assemble new type of rice varieties for high yield, biotic and abiotic stress resistance, with good quality rice is a solution to cope with food shortages. Polinela been assembling some new strains of rice germplasm by using superior character in quantity and quality. Research purposes (1) Knowing what superior character possessed by a new strain of rice Polinela assemblies, (2) Knowing where the strain that has a high yield potential. The study was conducted in Polinela April to August 2012. Research conducted with Randomize Completly Block Design (RCBD). Treatment consisted of 10 new strains of rice assemblies Polinela 4th generation (F4), repeated three times. To know the differences between the treatment then continued with Least Significant Different (LSD) on stage 5%. The variables measured were: maximum plant height, maximum number of shoots, number of productive shoots, number of grains per panicle, number of filled grains per panicle, panicle length, grain 1000 grain weight, grain yield per clump, and grain yield per hectare. Organoleptic tests carried out on the aroma and texture of rice or rice flavor. Results showed (1) All new rice strains quantitatively Polinela assemblies have a high yield potential, which is between 7.4 tonnes /ha until 10:34 tonnes /ha, (2) Strain B3, D2, D3, F2, and F3 have high yield potential between 8.4 tons / ha to 10.3 t / ha, as well as having quality taste fluffier rice with a slightly fragrant aroma (rather sweet) until fragrant (fragrant). Keywords: Power Test Results, ten strain of rice assemblies Polinela